The Role of Fathers in Children’s Character Development: A Literature Review - CHAQ, MOH. CHABLUL (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2024)
The role of fathers in shaping the character and emotional development of early childhood (0-6 years) is undeniably crucial. Fathers, with their unique parenting styles and approaches, contribute significantly to the formation of a child’s personality, moral values, emotional stability, and social skills. This literature review examines various studies to analyze the impact of father involvement on children’s character and emotional development. Research shows that fathers not only act as role models but also as key educators of moral values, providers of emotional support, and facilitators of social development. Active and positive father presence fosters a nurturing environment where children learn to trust, explore, and express themselves confidently. Furthermore, studies indicate that fathers who engage with their children in meaningful ways help cultivate emotional resilience, problem-solving skills, and an enhanced ability to navigate social interactions. The long-term impact of such involvement is reflected in children’s self-confidence, emotional intelligence, and preparedness to face future challenges, underlining the importance of father-child relationships in early childhood development.